Reliability and validity of the German version of the University of Jyvaskyla Active Aging Scale (UJACAS-G) - Timo Hinrichs; Taina Rantanen; Erja Portegijs; Lukas Nebiker; Roland Rössler; Fabian Schwendinger; Arno Schmidt-Trucksäss; Ralf Roth (SpringerOpen, 2024)
Abstract Background The University of Jyvaskyla Active Aging Scale (UJACAS) assesses active aging through willingness, ability, opportunity, and frequency of involvement in activities. Recognizing the lack of a German version, the Finnish original was translated (UJACAS-G). This study aimed: (1) to evaluate the test-retest reliability of UJACAS-G; and (2) to explore correlations with health-related parameters (concurrent validity). Methods The study (test-retest design) targeted healthy older adults aged 65+. Reliability of UJACAS-G (total and subscores) was assessed using Bland-Altman analyses and Intraclass Correlation Coefficients (ICCs). Furthermore, correlations (Spearman's rho) between UJACAS-G scores and physical function (walking speed, handgrip strength, balance, 6-minute walk distance), physical activity (International Physical Activity Questionnaire), life-space mobility (Life-Space Assessment), and health-related quality of life (Short Form-36 Health Survey) were calculated. Results Bland-Altman analyses (N = 60; mean age 72.3, SD 5.9 years; 50% women) revealed mean differences close to zero and narrow limits of agreement for all scores (total score: mean difference −1.9; limits −31.7 to 27.9). The ability subscore showed clustering at its upper limit. ICC was 0.829 (95% CI 0.730 to 0.894) for the total score and ranged between 0.530 and 0.876 for subscores (all p-values < 0.001). The total score correlated with walking speed (rho = 0.345; p = 0.008), physical activity (rho = 0.279; p = 0.033) and mental health (rho = 0.329; p = 0.010). Conclusions UJACAS-G is reliable for assessing active aging among German-speaking healthy older adults. A potential 'ceiling effect' regarding the ability subscore should be considered when applying UJACAS-G to well-functioning populations. Analyses of concurrent validity indicated only weak correlations with health-related parameters.